CORRELATION ANALYSIS OF VEHICLE FRONTAL IMPACT PARAMETERS - Josef Mík; Jana Kadlecová (Acta Polytechnica CTU Proceedings)
The article considers a possible improvement of road vehicle safety by using eCall – a system which initiates an emergency call in case of traffic accident. A possible way of better description of a frontal impact accident of a vehicle is examined and enriched by the information from the onboard e-call unit. In this article, we analyze results of frontal crash tests with different types of barriers and overlapping area and look for the correlation between the individual vehicle and collision parameters in order to provide a better description of the severity of the accident by the eCall system. The relation among the selected parameters is described using the correlation analysis.